Relación entre la flexibilidad psicológica y depresión en adultos - Pipa Beltrán, Maricielo Victoria (2022)
Depression is considered a limiting disorder because of the symptoms experienced by the individual, as well as the stressors to which he is exposed. Faced with this, it is essential to consider how people respond and relate to these experiences through psychological flexibility. This is defined as the ability to pay attention to the current moment and, depending on the context, change or persist in behavior in order to approach to the valued objectives. The present investigation aims to identify the relationship between psychological flexibility and depression in adults. For this purpose, a systematic search was carried out taking into account the guidelines of the "PRISMA" guide. For the analysis, ten scientific articles were selected that relate both variables and meet the inclusion and exclusion criteria. The results showed that there is a significant negative correlation between psychological flexibility and depression in adults; whereas contrast, psychological inflexibility, presents a positive correlation with depression. These findings suggest that the greater the presence of depressive symptoms, the less presence of psychological flexibility.